LA CONCEPTION DU FONCIER CHEZ LES PEUPLES AUTOCHTONES - Marie BOUNDAWANE , (IJRDO - Journal of Social Science and Humanities Research, 2019)
The present forest for the Pygmy populations a vital religious, political and economic stake.  Indeed, they count on the forest for their income, their medicines and their cultural identity.  However, the pressure anthropique caused by presence of the populations’ bantous and the forest operators on the spaces that the autochthonous peoples consider as their fundamental heritage poses a problem of occupation of earths and exploitation of the judicious fundamental heritage more and more to belong to the first occupants. This situation marginalizes this social category that already faces the denial of their right splicing doubly that people to the point to lose their culture if one doesn't make sure there.